The Relationship Between Energy, Protein, Vegetable and Fruit Intake and Infectious Diseases with Underweight Incidence Among Children Under Five in Sungai Bamban Village - Fitriati; Mas'Odah, Siti; Fathurrahman; Farhat, Yasir (Jurusan Gizi Poltekkes Kemenkes Banjarmasin, 2026)
In children under five, underweight remains a nutritional problem that can impair growth and increase susceptibility to illness. Underweight is influenced by inadequate nutrient intake, particularly energy and protein, low vegetable and fruit consumption, and the presence of infectious diseases. This study aimed to determine the relationship between energy, protein, vegetable and fruit intake and infectious diseases with underweight incidence among children under five in Sungai Bamban Village, working area of UPTD Rantau Badauh Health Center, in 2025. This study used an analytic observational method with a cross sectional design. The population was all children under five in Sungai Bamban Village, with a total sample of 79 children. The dependent variable was underweight status based on the weight-for-age index, while the independent variables were energy intake, protein intake, vegetable intake, fruit intake, and infectious diseases. Dietary data were collected using a Food Frequency Questionnaire (FFQ) and infectious disease history was obtained through interviews. Data analysis was performed using the Chi-square test. The results showed that 26.6% of children were underweight. As many as 46.8% had inadequate energy intake, 50.6% had inadequate protein intake, 60.8% had low vegetable intake, 51.9% had low fruit intake, and 45.6% had a history of infectious diseases. There were significant relationships between energy, protein, vegetable and fruit intake, infectious diseases, and underweight incidence among children under five (p<0.05). Families are expected to improve children's dietary quality by ensuring adequate energy and protein intake, increasing vegetable and fruit consumption, and preventing and managing infectious diseases through appropriate health services